PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT GLOBAL SARANA SUKSES DI JAKARTA SELATAN - Muhamad Rifki Ihsan Azhari; Endah Mawarny (Journal of Research and Publication Innovation, 2025)
The objective of this study was to examine the positive and significant impact of competence and work discipline on employee performance at PT Global Sarana Sukses. The population in this study is 60 respondents and the sample gathered by Slovin's formula is 60 respondents. Data collection techniques taken from both primary and secondary data sources. The research method employed was quantitative with an associative approach. The results indicated that: (1) competency has a positive partial effect on employee performance, as evidenced by the linear regression test, which is the regression equation of Y = 3.664, + 0.448X₁ and the constant value is 3.664. The value of ????test 1.175 with the 5% distribution table value of 1.67155, while the ????test 1.175> ????????able 1.67155 it showed a significant level <0.05 which is 0.001. (2) The results showed that work discipline has a positive partial effect on employee performance, as demonstrated by the linear regression test, which is showed on a regression equation of Y = 1.175 + 0.485X₂. This indicates that the constant value is 1.175 The t test has a value of ????test 5.217 with the 5% distribution table value of 1.67155, while the ????test 5.217 > ????table 1.67155 it showed a significant level <0.05 which is 0.000. The results showed that work discipline has a positive effect on employee performance. (3) Simultaneously, competency and work discipline have a positive impact on employee performance as presented by the linear regression test, which is showed on a regression equation of Y = 3.664 + 0.448X₁ + 0.485X2.